FLASH ultra-high dose rates in radiotherapy: preclinical and radiobiological evidence. (1st February 2022) - Borghini, Andrea; Vecoli, Cecilia; Labate, Luca; Panetta, Daniele; Andreassi, Maria Grazia; Gizzi, Leonida A.
Abstract: Purpose: Flash radiotherapy (FLASH-RT) is currently being regarded as the next breakthrough in radiation treatment of cancer, delivering ultrahigh radiation doses in a very short time, and sparing normal tissues from detrimental injury. Here we review the current evidence on the preclinical findings as well as the radiobiological mechanisms underlying the FLASH effect. We also briefly examine the scenario of available technologies for delivering FLASH dose-rates for research and their implications for future clinical use. Conclusions: Preclinical studies report that the FLASH-RT reduces radiation-induced toxicity whilst maintaining an equivalent tumor response across different animal models. However, the molecular radiobiology underlying FLASH effect is not fully understood and further experiments are necessary to understand the biological response. Future studies also includes the design of a FLASH delivery system able to produce beams appropriate for treatment of tumors with ultra-high dose rates. All these research activities will greatly benefit from a multidisciplinary collaboration across biology, physics and clinical oncology, increasing the potential of a rapid clinical translation of FLASH-RT.